Protection of groundwater resources from multi-hazards: An integration of risk assessment and watershed management - Lima, Victor Hugo Sarrazin; Pacheco, Fernando António Leal; Moura, João Paulo; Pissarra, Teresa Cristina Tarlé [UNESP]; do Valle Junior, Renato Farias; de Melo Silva, Maytê Maria Abreu Pires; Monteiro da Costa, Adriana; Valera, Carlos Alberto; de Melo, Marília Carvalho; Sanches Fernandes, Luís Filipe (My University, 2024)
Mining areas are abundant in this basin and were allocated high values of H and low to high values of V, requesting implementation of groundwater monitoring and periodic inspection of mining sites, even more because groundwater contamination with iron could be clearly associated with the presence of mine-tailings. The improving groundwater resource protection depends on aligning contamination risk mapping with aquifer protection measures. However, existing methods often fail to align with aquifer protection goals, hindering practical implementation. The study demonstrated integrating vulnerability assessment, hazard evaluation, and groundwater protection initiatives using an L-Matrix approach. Testing this model in a well-documented watershed with multiple hazards to illustrates its applicability, providing a reference for similar scenarios. The risk was assessed through evaluation of aquifer vulnerability, using the DRASTIC method, coupled with the evaluation of a hazard potential considering industrial, livestock/agriculture and urban infrastructure sources in separate. The L-Matrix diagrams consisted of cartesian representations of V versus H, ranging from 0 to 1, segmented into four quadrants bounded by the cut-off lines V = 0.5 and H = 0.5. The quadrants were then linked to aquifer protection measures, with site inspection (high V and H), groundwater monitoring (low V and high H), land use planning (high V and low H), and tolerable expansion of hazardous activities (low V and H). The Paraopeba River basin was used as test site. Mining areas are abundant in this basin and were allocated high values of H and low to high values of V, requesting implementation of groundwater monitoring and periodic inspection of mining sites, even more because groundwater contamination with iron could be clearly associated with the presence of mine-tailings. In the results, it was observed that the DRASTIC vulnerability map of the aquifers has a mean vulnerability around the central value (V = 0.48 ± 0.08). Regarding the distribution of hazards, the average rounds to the value for to (Hindustry = 0.41 ± 0.37, Hagriculture = 0.33 ± 0.09 and Hinfrastructure = 0.27 ± 0.14). Thus, it is noted that for industrial activities, the risk of contamination could be moderate to high, while for agricultural and livestock activities, the risk lies between low and moderate contamination impact.
Keywords: Aquifer protection measures; Groundwater contamination risk; Iron contamination; L-matrix diagram; Mine tailings; Paraopeba river basin